Technology Adoption in Higher Education Case Study: University Student in Labuhanbatu - Munthe, Rika Syahmewah; Zarkasih, Amron; Wahyuni, Erni; Mandili, Irhamna (CV. Inara, 2022)
The online learning system has become an indispensable solution for educational institutions during the COVID-19 period. Therefore, if we take a closer look at the findings of this study, it is evident that the students are working hard to overcome the challenges of the online learning system. Learning and teaching activities must continue to be carried out even though COVID-19 still exists, educational institutions must immediately adapt so that they can continue to run as they should. The use of online learning media using relevant software is certainly a new demand in the world of education. Every change certainly takes time to adapt to the new thing. The online learning system also takes time to be accepted by students. In this study, researchers wanted to examine the effect of perceived ease of use, perceived usefulness and perceived quality of the system on the intention to use online learning tools. This study was conducted in Labuhanbatu with the sample being students in Labuhanbatu district who had undergone online learning during the COVID-19 pandemic. This study uses a quantitative approach and the analytical method used is Partial Least Square with the help of SMART PLS 3 software. It is hoped that this research can provide input to universities in order to improve the quality of learning with online learning methods.